Pengaruh Pendayagunaan Zakat Produktif Terhadap Pemberdayaan Mustahiq: Studi Kasus Lembaga Amil Zakat Infaq Shadaqah (LAZISNU) Kulon Progo - Thoha Yasin Utsman; Syamsul Ma'arif; Silda Labibi (Tasharruf : Journal of Islamic Economics and Business, 2022)
The formulation of the problem in this study is how the influence of the use of productive zakat on the empowerment of LAZISNU KulonProgo mustahiq. Therefore the purpose of this study is to determine the effect of the use of productive zakat on the empowerment of LAZISNU KulonProgo mustahiq. This research uses quantitative methods with a regression equation is a field research. Sources of data in the form of primary data and secondary data. Data collection techniques consist of observation, interview, questionnaire ,. The population in this study amounted to 200 mustahiq or respondents and the sample in this study amounted to 66 mustahiq or respondents using the Slovin sample size determination technique. For the process of data analysis using simple regression analysis, the use of productive zakat as an independent variable and the empowerment of mustahiq as the dependent variable. Based on the results of research conducted by the author, the utilization variable of productive zakat has a positive and significant influence on the empowerment variable mustahiq. Keywords: Productive Zakat, Empowerment of Mustahiq, Utilization of Zakat